Students' Boredom Profile in Mathematical Problem-Solving: A Computational Thinking Perspective - Rahmawati, Fadila; Nizaruddin, Nizaruddin; Murtianto, Yanuar Hery (Jurnal Pendidikan MIPA, 2025)
Boredom is a mental state characterized by discomfort and dissatisfaction caused by insufficient introduction of stimulus, challenge, or meaning in the environment. Objective: This study aims to describe students' boredom profile in solving mathematics problems based on their computational thinking ability. Methods: The method used was a descriptive qualitative approach with the subject of 62 students consisting of 63% female students and 37% male students of class IX SMP Negeri 1 Semarang, then took nine students with purposive sampling technique, taking subjects based on advanced, intermediate, and basic computational thinking ability tests, taken three each category based on recommendations from subject teachers. Findings: Student boredom is influenced by five factors, namely disengagement, high arousal, inattention, low arousal, and time perception. Students with advanced computational thinking ability generally do not feel bored because they feel challenged, although they can lose interest if the problem is too easy. Students with intermediate computational thinking ability have relatively low boredom, remaining engaged despite difficulties. In contrast, students with basic computational thinking ability are more susceptible to boredom due to difficulty understanding problems, frustration, a desire to quit, and a perceived lack of engaging activities. To overcome the problem of boredom, the recommendation from this study is to provide content-differentiated learning for each student, this can also be a recommendation for further research. Conclusion: Students with advanced computational thinking can feel bored if the problems given are too easy. Meanwhile, students with basic computational thinking feel bored when they find it difficult to understand the problem.       Keywords: boredom, mathematics, problem-solving, computational thinking.